The Effectiveness of Roundtable Technique on Students’ Writing Ability in Descriptive Text - Rosidah, Khulaefatur (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study aims to describe the effectiveness of using the Roundtable Technique in improving students' descriptive writing skills at the seventh grade of Darussalam Islamic Junior High School, Bojonegoro. The research also compares the outcomes of descriptive writing using the Roundtable Technique with the Make-a-Match Technique and evaluates the improvement in students' scores. A pre-experimental one-group pre-test and post-test design was employed. The study involved 30 students as the sample, and data were analysed using a paired sample t-test to determine significant differences before and after treatment. The findings reveal a significant improvement in students' descriptive writing ability following the application of the Roundtable Technique. This is demonstrated by an increase in the mean score from 73.60 in the pre-test to 83.03 in the post-test. The paired sample t-test results showed a p-value of 0.00, which is lower than the significance level of 0.05, indicating a significant effect. Consequently, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. These results highlight that the Roundtable Technique effectively enhances students' descriptive writing skills, providing a beneficial method for teaching writing in junior high school contexts.